Laryngeal Web as a Possible Cause for Nonabsorption of Vocal Nodules in Boys After Puberty - Garcia Martins, Regina Helena [UNESP] (2019)
Objectives: Vocal nodules are frequent in children and tend to be reabsorbed after puberty, especially in boys. The aims of the present study were to analyze the progression of nodules in boys after puberty and to investigate the role of microweb in the persistence of these lesions. Methods: Clinical and videolaryngoscopy evaluations were carried out in boys with vocal nodules treated between 2009 and 2016, followed up to the age of 17 years or until remission of symptoms and reabsorption of the nodules. Boys with vocal nodules who underwent regular vocal therapy are included in the study. The outcomes were remission of symptoms and of the nodular lesions. Results: A total of 34 boys with vocal nodules were diagnosed, of which 21 completed follow-up. Mean age of the first evaluation was 9 years (5-11 years) and of end of treatment was 14 years (13-18 years). Mean number of videolaryngoscopy per child was five. After adolescence there was complete remission of symptoms and of the lesions in 15 children (71.4%), partial remission in four (19.0%), and no remission of symptoms and of the lesions in two cases. In these two, videolaryngoscopy identified the presence of microweb and nodules. Conclusions: Favorable reabsorption of the vocal nodules after adolescence was observed in the majority of the boys who underwent voice therapy; however, in two cases there was no remission of symptoms and of the lesions. The unfavorable course can be attributed to anterior laryngeal microwebs.